"Repuesta de la pitahaya roja (Hylocerreus undatus) a la aplicación de dos abonos orgánicos sólidos en distintas dosis en la zona de San Carlos". - Cruz Sánchez, José Eduardo (2016)
The pitahaya is belonging to the family of cacti and develops in tropical locations. According to the Census of Agriculture conducted by the National Institute of Statistics and Census (INEC) in 2010, the cultivated exclusively in Ecuador, pitahaya area was 235 hectares, which represents a minimum production of the fruit. The main objective of this research was evaluate the response of the red dragon fruit (Hylocereus undatus) the application of two solid manure application rate in three agro-ecological conditions in San Carlos. This research was conducted from June 2015 until September at the "Phoenix" Mr. Segundo Amaguaya property, located in the Parish San Carlo, Los Rios Province. 315 plants of the genus (Hylocereus undatus) used, load factors were studied organic fertilizers (Humus and compost) in doses 8; 4 and 2 t ha-1. Design of complete random (DBCA) with seven treatments and three repetitions was used blocks. To measure the differences between treatment means the multiple range test of Tukey (p ≤ 0.05) was used. The variables studied were as follows; number of outbreaks, days to flowering, number of fruits, fruit diameter, fruit length, fruit weight and yield per hectare. The main results obtained were as follows; organic fertilizers (humus and compost) used in this experiment to crop fertilization pitahaya showed a similar effect when they were used in the same doses; each of the variables tested had a downward trend decreased as the dose of fertilizer applied. Allowed dose maximize performance in growing pitahaya (Hylocereus undatus) in both types of compost was 8 t ha-1. Keywords: Humus, compost, Pitahaya, Organic Fertilizers